Airway obstruction and lung hyperinflation in COPD are linked to an impaired left ventricular diastolic filling. (April 2018) - Alter, Peter; Watz, Henrik; Kahnert, Kathrin; Pfeifer, Michael; Randerath, Winfried J.; Andreas, Stefan; Waschki, Benjamin; Kleibrink, Björn E.; Welte, Tobias; Bals, Robert; Schulz, Holger; Biertz, Frank; et al.
Abstract: Aims: Chronic obstructive pulmonary disease (COPD) and cardiovascular diseases are thought to be linked through various factors. We aimed to assess the relationship between airway obstruction, lung hyperinflation and diastolic filling in COPD. Methods: The study population was a subset of the COPD cohort COSYCONET. Echocardiographic parameters included the left atrial diameter (LA), early (E) and late (A) transmitral flow, mitral annulus velocity (e'), E wave deceleration time (E[dt]), and isovolumic relaxation time (IVRT). We quantified the effect of various predictors including forced expiratory volume in 1 s (FEV1 ) and intrathoracic gas volume (ITGV) on the echocardiographic parameters by multiple linear regression and integrated the relationships into a path analysis model. Results: A total of 615 COPD patients were included (mean FEV1 52.6% predicted). In addition to influences of age, BMI and blood pressure, ITGV was positively related to e'-septal and negatively to LA, FEV1 positively to E(dt) (p < 0.05 each). The effect of predictors was most pronounced for LA, e'-septal and E(dt), and less for E/A, IVRT and E/e'. Path analysis was used to take into account the additional relationships between the echocardiographic parameters themselves, demonstrating that their associations with the predictors were maintained and robust. Conclusions: Airway obstruction and lung hyperinflation were significantly associated with cardiac diastolic filling in patients with COPD, suggesting a decreased preload rather than an inherently impaired myocardial relaxation itself. This suggests that a reduction in obstruction and hyperinflation could help to improve cardiac filling. Highlights: COSYCONET is an observational, multicenter cohort study in patients with COPD. Airway obstruction and lung hyperinflation were associated with diastolic filling. Functional impairment of the lung leads to a decreased left heart preload and filling by mechanical interactions. The prevalence of myocardial diastolic dysfunction appears to be lower in COPD than expected. It is suggested that a reduction in obstruction and hyperinflation could improve cardiac filling.